The politics of sexual harassment : a comparative study of the United States, the European Union, and Germany - Zippel, Kathrin S. (Cambridge University Press, 2006)
Kathrin Zippel explores the globalization and diffusion of the concept of sexual harassment from the US to Europe, and the different paths countries have embarked on to change employers' practices and the culture in the workplace. Comparative and uniquely comprehensive, it will appeal to students and scholars alike.